DNA fingerprinting and serotyping of Campylobacter jejuni isolates from epidemic outbreaks. - Lind, L (1996)
The aim of the present investigation was to compare DNA fingerprinting and serotyping (heat-stabile and heat-labile antigens) of isolates from epidemic outbreaks as well as of solitary isolates. Campylobacter jejuni isolates from two epidemic outbreaks in Sweden, one milkborne (35 isolates) and one waterborne (17 isolates), and one waterborne outbreak in Norway (11 isolates), as well as 30 solitary isolates from Swedish patients with gastroenteritis, were analyzed. A total of 93 isolates were analyzed. In the waterborne outbreak in Norway, only one serotype with one DNA pattern was found. In the milkborne outbreak in Sweden, two serotypes (HS2:HL4 and HSNT:HL4) with two different DNA patterns were found. The isolates from the waterborne outbreak in Sweden were different serotypes. For two isolates of the same serotype, different DNA patterns were seen. This was also recorded for isolates from solitary cases. It was concluded that serotyping is a useful tool in most epidemiological situations but sometimes lacks sufficient discriminatory power. DNA fingerprinting can add valuable epidemiological information to that supplied by serotyping and can in some situations provide sufficient epidemiological information when used alone.